PENGARUH PENERAPAN TEORI BELAJAR BRUNER TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS III SEKOLAH DASAR - Ramadania, Ramadania; Hamdani, Hamdani; Uliyanti, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to analyze the influence of the application of Bruner learning theory to the mathematics learning outcomes of grade III student of SD Negeri 54 Pontianak Barat. The methodology used for this study is all the grade III students of SD Negeri 54 Pontianak Barat. The sample was decided by using sampling purposive technique which resulted grade III A with 30 students as the sample. The data collection technique that was used were measurement technique. The data collecting tools used were essay test containts 5 question. Base on the data analysis, the results that were obtains are average of students pre-test result are 59,73 and the average of students post-test are 73,70. After the t-test, it is found that the tcount is 5,777 with ttable (? = 0,05 dan dk = 30-1 = 29) are 2,045. Because the tcount > ttable, it is concluded that Ha is accepted. So it can be concluded that the application of Bruner learning theory has influenced the mathematics of grade III students of SD Negeri 54 Pontianak Barat. Keywords: Bruner Learning Theori, Mathematics, Learning Outcomes